Utilization of plant bioactives as feed additives for poultry: The effect of Aloe vera gel and its extract on performance of broilers - Sinurat, A.P; Purwadaria, T; Togatorop, M.H; Pasaribu, T (Indonesian Journal of Animal and Veterinary Sciences, 2003)
Feed additives are commonly added in poultry feed as a growth promotant or to improve feed efficiency. The most common feed additive used is antibiotic at sub-therapheutic doses, although there is a controversy on its impact on human health. Previous results showed that Aloe vera gel could improve feed efficiency in broilers and an in vitro study showed that the extract have an antibacterial effect. Therefore, a further experiment was designed to study the response of broilers to Aloe vera gel or its extract as feed additives. Aloe vera was prepared in dry gel or chloroform-extract and included in the diet at levels of 0.25; 0.50 and 1.00 g/kg (equal to dry gel). Standard diets with or without antibiotic were also formulated as control and a commercial diet was included for comparison. The diets were fed to broilers from day old to 5 weeks. Each treatment has 9 replicates and 6chicks/replicate. Parameters observed were: feed consumption, weight gain and feed convertion ratios. Carcass yield, abdominal fat levels, relative weight of liver, gizzard, tractus digestivus and length of tractus digestivus were also measured at the end of feeding trial. The results showed that Aloe gel and its extract did not influence body weight gain and feed consumption of broilers significantly (P>0.05), but improved feed convertion slightly (3.50%). The response in this trial was similar as thosecommercial diet and diet added with antibiotic. There was no significant (P>0.05) effect of Aloe vera bioactives on carcass yield, abdominal fat level and relative weight of liver. However, Aloe vera gel and its extract tend to increase gizzard weight, gastro intestinal weight and length. The Aloe vera gel and its extract also reduced the total count of aerobic bacteria in the digesta of tractus digestivus. It is concluded that the Aloe vera gel improve feed efficiency in broilers by increasing the size of tractus digestivus and reducing the total count of aerobic bacteria in the gastro intestinal tract. Â  Key words: Aloe vera, feed additives, broilers, anti-bacteria